2020
DOI: 10.1111/hsc.13029
|View full text |Cite
|
Sign up to set email alerts
|

The child’s got a complete circle around him”. The care of younger children (5–11 years) with CFS/ME. A qualitative study comparing families’, teachers’ and clinicians’ perspectives’

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…It is worthy of note that carers felt the need to take on a number of roles that were normally performed by other people and that this is likely to have impacted their ability to do other roles such as “normal” parenting and other aspects of their life including self-care. 17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthy of note that carers felt the need to take on a number of roles that were normally performed by other people and that this is likely to have impacted their ability to do other roles such as “normal” parenting and other aspects of their life including self-care. 17…”
Section: Discussionmentioning
confidence: 99%
“…10,[13][14][15] A recent study examining the roles of parents, clinicians, and teachers of primary aged children with ME/CFS indicated that each had different roles. 17 The study suggested that the clinician was responsible for diagnosis and treatment planning, while the teachers were responsible for the daily management of the child's health while they were at school. The parent was responsible for the coordination of care, the supervision of treatment, and monitoring their symptoms and activity levels.…”
mentioning
confidence: 99%
“…For CYP with CFS/ME, disrupted schooling 'has a significant impact on the self (resulting) in a shift from a perceived normal trajectory of academic achievement and independence to one that is uncertain' (p.10), 24 and some educational support and adaptations underpinned by evidence-based awarenessraising in schools have been recommended. [25][26][27][28]…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Most research to date focuses on quantitative outcomes of school absenteeism and academic achievement (Sankey et al, 2006 ; Tollit et al, 2018 ), failing to detail the wider experiences of adolescents with ME/CFS when engaging with schools and the education system. One study investigated the role of primary schools in the care of young children with ME/CFS (Brigden et al, 2020 ), but is limited in its application to adolescents. There is little qualitative research about adolescents' views on managing ME/CFS in secondary education.…”
Section: Introductionmentioning
confidence: 99%